(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The aim of this research is to assess the effectiveness of an on-the-job training program on employee performance at Pacific Air-conditioning and General Services, Inc. in terms of dependability, quality of work, quantity of work, work attitude, Knowledge, & Technical Expertise. According to the findings of this study, PAGS Inc. workers have an average age of 32-37 years old, are mostly male, work full time, and have held the post of Project Engineer for 4-5 years; the efficacy is rated as "highly effective" in terms of the degree of employees’ performance of Pacific Air-conditioning General Services Inc.; the challenges encountered by the employees in terms of On-the-job training program was lack of feedback on training; there is also a recommendation for improving Pacific Air-conditioning and General Services, Inc.s’ on-the-job training programs in order to increase staff performance. According to the findings of this study, while employees are receiving on-the-job training, the mentor or trainer should provide regular feedback to them so that they are aware of their development. Giving feedback is essential for informing your team members about their performance and expectations. It also contributes to team growth and development. This feedback must be given on a frequent and ongoing basis, not simply at performance appraisals.